Factors mediating Acinetobacter baumannii biofilm formation: Opportunities for developing therapeutics - Upmanyu, Kirti; Haq, Qazi Mohd. Rizwanul; Singh, Ruchi (Current research in microbial sciences, 2022)
•A. baumannii rapidly acquires antimicrobial resistance and causes biofilm associated infections.•Strategies to target intrinsic factors mediating A. baumannii biofilm formation offer therapeutic prospects.•Antimicrobial polymers and coating medical devices with antibiofilm agents may prevent biofilm associated infections.•Biofilm matrix or regulatory mechanisms such as quorum sensing are potential targets for treating chronic infections.•Phage therapy, photodynamic therapy and nanoparticle therapy are novel promising approaches for treating biofilm associated infections. Acinetobacter baumannii has notably become a superbug due to its mounting risk of infection and escalating rates of antimicrobial resistance, including colistin, the last-resort antibiotic. Its propensity to form biofilm on biotic and abiotic surfaces has contributed to the majority of nosocomial infections. Bacterial cells in biofilms are resistant to antibiotics and host immune response, and pose challenges in treatment. Therefore current scenario urgently requires the development of novel therapeutic strategies for successful treatment outcomes. This article provides a holistic understanding of sequential events and regulatory mechanisms directing A. baumannii biofilm formation. Understanding the key factors functioning and regulating the biofilm machinery of A. baumannii will provide us insight to develop novel approaches to combat A. baumannii infections. Further, the review article deliberates promising strategies for the prevention of biofilm formation on medically relevant substances and potential therapeutic strategies for the eradication of preformed biofilms which can help tackle biofilm-associated A. baumannii infections. Advances in emerging therapeutic opportunities such as phage therapy, nanoparticle therapy and photodynamic therapy are also discussed to comprehend the current scenario and future outlook for the development of successful treatment against biofilm-associated A. baumannii infections. [Display omitted]